Caracterización físico – química y mineralógica del material de mena proveniente de la concesión minera “Los Cipreces”, código catastral 300302, ubicada en la parroquia Huertas, cantón Zaruma, provincia de El Oro. - Ojeda Carrión, Fabricio Xavier (2025)
The purpose of this research was to characterize the physical, chemical and mineralogical characteristics of the ore material from the mining concession "Los Cipreces ", in order to study the nature of the minerals and evaluate the best metallurgical recovery technique. Under this foundation, from a previous sampling of the Cristina vein, its properties were identified through the following laboratory tests: for the physical properties, moisture content tests, actual specific weight, apparent specific weight and porosity were analyzed; for the chemical properties, analytical techniques of fire assay and atomic absorption spectrometry were developed; and for the mineralogical properties, X-ray analysis techniques were performed: X-ray Diffraction (XRD) and X-ray Fluorescence (XRF), macroscopic characterizations of hand samples and optical mineralogical analysis with thin sections using Parallel Polarized Light (PPL) and Cross Polarized Light (CPL). The results obtained indicated that the samples present a relatively dense structure with a restricted fraction of pore volume. They showed different mineral concentrations, with a significant content of gold (Au) and silver (Ag) head grade. The XRD analysis detected the presence of sulfides (chalcopyrite and sphalerite) and the XRF complemented the analysis, revealing significant concentrations of Si, Fe and S, together with other trace elements, such as As, Pb, Zn. The LPP and LPX optical analyses identified a propylitic alteration and an epidote/chlorite paragenesis and carbonates. Finally, a low recovery of valuable minerals was identified when subjected to a direct cyanidation process due to the presence of sulfides (refractory minerals). Keywords: epithermal deposit, materials characterization, analytical tests, refractory minerals, mineral beneficiation.